ENT 530 Social Media Portfolio: Churro Chu'go / Nurshasya Nabila Idham Khalil - Idham Khalil, Nurshasya Nabila (2021)
Churro Chu'Go is a dessert specialty store that will provide everyone with the sweetness of life and the most delicious Churros they have ever tasted. Taste the delicious Churros that we made with love and joy, paired with refreshing ice cream and a variety of toppings from which they can choose. As we know, Churros is a traditional doughnut from Spain, which in Malaysia is becoming widely known. Churro Chu'Go has a great opportunity to start up and enter the market because the chance to compete in this market is reasonably decent. Churro Chu'Go is a fresh new idea that distinguishes our product from another offering. Churo Chu'Go is located at Lot P1-22, Shaftsbury Square, Persiaran Multimedia, Cyber 6, 63000 Cyberjaya, Selangor. Churo Chu’Go has started in January 2020. Our mission is to be the market leader in the food stand industry in Malaysia, providing high quality product with affordable price for our customer. To ensure that our Churros stay flavorful and satisfy our clients, we always use the greatest ingredients and make sure our batter is the best. In the minds of our customers, we want to be the first choice of Churros. Our company name was inspired by our first product, which holds a particular place in our hearts. Hopefully, it will serve as a constant reminder to our customers of how this brand developed. Our main strategy is to allow people to enjoy Churros whenever they desire a snack product. We also aim to make Churros the breakfast food of choice here, as restaurants in Spain serve Churros every day for their breakfast. What distinguishes our product from others is our effort to prepare the dough using our own recipes in order to achieve the desired taste. We also provides a variety of flavors and toppings for our customers to choose from according on their preferences.